KASUS ABORSI DAN PEMBUANGAN BAYI SEBAGAI KEPRIHATINAN GEREJA DAN IMPERATIF EDUKATIFNYA BAGI DUNIA PENDIDIKAN - Yohanes S. Lon (JIPD (Jurnal Inovasi Pendidikan Dasar), 2020)
The disposal of infants and criminal provocatus abortion committed by students have been a concern of the Manggarai community today. According to Indonesian state law and the teachings of the Church, the two acts violate the law, norms and ethics in society and religion. These actions result in eliminating lives that are believed to originate from God. This research found that they are caused by free sex behavior, lack of sexual education and lack of pro-life culture and pro-life education. Therefore, this article recommends that educational institutions and religious institutions, especially Catholic religions should be more active in promoting sexual education for adolescents, building a pro-life culture for the whole community and developing effective pastoral care. Churches and educational institutions should not only function to provide social, religious and educational sanctions, but mainly to become institutions that are present in the suffering and anxiety of young people who are entangled in problems. By doing such things, the disposal of infants and abortion cases are expected to be reduced or lost.